Enhancing Language Skills in Autistic Children: A Psycholinguistic Exploration of ABA Therapy Effects with Linguistic and Psycho-Behavioral Perspective - Nidya Fitri; Dewa Ayu Widiasri (Universitas PGRI Sumatera Barat, 2024)
The study was conducted to analyze the effect of ABA therapy on the language skills of autistic children: a psycholinguistic review. The cause of language disorders in autistic children is that there are nervous system disorders in the brain. Developmental disorders require further treatment in order to improve children's language skills. The method used was pre-experiment with one group pre-test and posttest design with statistical tests such as the Wilcoxon test. Analysis techniques using ABC (Antecedent, Behavior, Consequence) models with parameters of compliance, imitation skills, and establishing eye contact. The research was conducted in one of the training places for children with special needs in the city of Pekan Baru. The child population of 15 autistic children with eight children was sampled for language disorders. The development of the application of ABA therapy is carried out for three months. The results of the Wilcoxon sign rank test on the pre-test and posttest showed a significant increase in bye-bye, applause, spinning, and jumping activities with a significance value of 0.045. ABA therapy in autistic children is one of the behavioral therapies that focuses on handling the situation when the child is able to respond correctly. Through the application of ABA therapy, children are able to respond according to the instructions given by the therapist.